A study showing efficacy of harmonic scalpel over electrocautery in modified radical mastectomy - N., Anandaravi B.; Nair, Praveen P.; Aslam, Mohammed Anwar (International Surgery Journal, 2017)
Background: The dissection in breast surgeries can be done using sharp scalpel and scissor dissection and high frequency electrocautery. Rarely, radiofrequency ablation and laser had been used in some limited trails. This study aims to prove the efficacy of harmonic scalpel over electrocautery in modified radical mastectomy operation. Methods: In this study, we included 40 patients with operable breast cancer. The patients were randomized into two equal groups by closed envelope technique to do modified radical mastectomy either using harmonic scalpel (group A) or using electrocautery (group B). The efficacy of two procedures were compared intraoperatively and postoperatively. The intraoperative parameters used were total time taken for surgery, time taken for axillary dissection, time for raising the flaps and time taken dissection of the breast tissue and the amount of blood loss. The post-operative parameters used were total drainage volume, days of drainage and seroma formation. Results: Our study showed use of harmonic sclalpel in modified radical mastectomy, resulted in reduction in total operating time (t= 4.037, p=0.00) as well as reduction in time taken for axillary dissection (t=3.66, p=0.001) and the amount of blood loss (t=3.02, p=0.00). The total drain volume (t=3.031, p=0.004) and the days of drainage (t=5.97, p=0.00) were also less with the harmonic scalpel dissection as compared to electrocautery. Conclusions: The use of harmonic scalpel in modified radical mastectomy shortens the operating time, axillary dissection time, amount of blood loss and drainage volume and drainage day and hence the hospital stay.